2020
DOI: 10.1007/s00382-020-05519-5
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation response to extreme soil moisture conditions over the Mediterranean

Abstract: The intimate link between soil moisture and precipitation makes it a “chicken-and-egg situation” that challenges climate studies of the continental water cycle. This association is particularly acute over the Mediterranean, increasingly exposed to droughts with climate change. This study aims at deciphering the impact of spring soil moisture state in the Mediterranean on subsequent warm season precipitation. In an idealized setup, two distinct climate models are used to generate extreme dry or wet soil conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Most of these experiments are also described and used in the Ardilouze et al (2020) companion study, which analyzes the precipitation response to soil water extreme conditions. The large perturbation for initialization of the dry and wet experiments was necessary to reach very low water content in the soil, close to the wilting point (SXP-DI) and field capacity (SXP-WI) by the beginning of the summer.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these experiments are also described and used in the Ardilouze et al (2020) companion study, which analyzes the precipitation response to soil water extreme conditions. The large perturbation for initialization of the dry and wet experiments was necessary to reach very low water content in the soil, close to the wilting point (SXP-DI) and field capacity (SXP-WI) by the beginning of the summer.…”
Section: Experimental Designmentioning
confidence: 99%
“…7c, d) become remarkable after the end of the summer: while in the coupled SXPs Tmax90 is indistinguishable from EXP-B0, in the prescribed runs the difference between Tmax90 DP and Tmax90 B0 increases in September-October. The impact on Tmax and Tmax90 is further reinforced by an increase in sensible heat flux, due to a marked precipitation reduction (Ardilouze et al 2020).…”
Section: Dry Sensitivity Experimentsmentioning
confidence: 99%
“…The differences between regions are both dependent on the local expression of the climate forcing and watershed characteristics. Because those physical processes are interacting, studying cross-scale interactions in precipitation brings more insight on the dynamics behind the spectral characteristics of each region (Boé, 2013;Materia et al, 2021;Bellucci et al, 2015;Ardilouze et al, 2020).…”
Section: Time Frequency Patternsmentioning
confidence: 99%
“…6a), which in contradiction with recent literature. For instance, in the Mediterranean region, Ardilouze et al (2020) found no negative soil moisture precipitation feedback for interannual scales; however, the authors used two climate models to simulate soil moisture sensitivity to precipitation forcing and note that this variability is much larger in century-long reanalysis, such as NOAA's 20CR. For other regions, interannual negative soil moisture feedback was found by Boé (2013), while Sejas et al (2014) found negative ocean-land temperature differences in precipitation feedback.…”
Section: Cross-scale Interactionsmentioning
confidence: 99%
See 1 more Smart Citation